HUBUNGAN PENGETAHUAN KEBUDAYAAN PRANCIS DAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS BAHASA PRANCIS. - Siti Renggo Geni ZEN (BAHAS, 2008)
The research was intended to determine the relationship between (1) The Knowledge of French Cultural and the Ability of Writing French, (2) the Reading Comprehension Mastery and the Ability of Writing French and (3) the Knowledge of French Cutural with the Reading Comprehension Mastery and the Ability of Writing French. The result of the research indicate positive correlation between (1) the Knowledge of French Cultural and th Ability of Writing French, (2) the Reading Comprehension Mastery and the Ability of Writing French and (3) the Knowledge of French Cultural with the Reading Comprehension Mastery and the Ability of Writing French.     Kata Kunci : Pengetahuan Kebudayaan, Membaca Pemahaman, Keterampilan Menulis